(untitled) (DAPesquisa, 2025)
ABSTRACT This article aims to examine, from the perspective of Intellectual Property, the emblematic legal dispute between Christian Louboutin and Yves Saint Laurent, which falls within the emerging field of Fashion Law. Based on theoretical foundations in specialized doctrine, comparative case law analysis, both at national and international level, and study of the relevant legislation, the article investigates the possibility of legal protection of color, especially when used as a distinctive element of visual identity and registered as a trademark. The case in question raises relevant reflections on the limits between legitimate creation and undue reproduction (copy), the construction of trademark identity and the legal and market effects resulting from the decision. Finally, the article discusses the impact of this precedent on the global fashion scenario, highlighting the growing importance of protecting intangible and symbolic assets in the sector. Keywords: Intellectual Property; Fashion Law; Color Trademark; Visual Identity; Louboutin; YSL.